The Diagrams Books - Kevin Duncan (LID Publishing)
People find it difficult to express ideas and solve problems purely with words. They find it much easier to use diagrams. Distilled into this single, handy-sized volume are 50 of the most useful diagrams, which are used by consultants, academics, MBA students and smart managers globally to aid their problem-solving and thinking. Triangle and pyramids, grids and axes, timelines, flows and concepts, circles the 50 diagrams are each visually presented and then explained in an accessible manner, including tips and advice on how you can apply them to your own situations.